On Generalized Leftly e ─ Core Transference - Mahmood, Ammar; Mohammed, Hanan (Iraqi Journal of Science, 2023)
Richards in 1996 introduced the idea of leftly e ─ core transference by using many conditions, including that the difference between the colums (k) is greater than of weight. In this paper, we generalized this idea without the condition of Richards depending on the mathematical and computational solution.